Prudential supervisory disclosure (PSD) with supervisory technology (SupTech): lessons from a FinTech crisis - Stefan Zeranski; Ibrahim E. Sancak (International Journal of Disclosure and Governance, 2021)
The U.S. financial markets faced an unprecedented rapid decline and recovery on May 6, 2010, known as the May 6 flash crash. Roughly one trillion market value in less than thirty minutes vanished with the biggest one-day point decline in the history of the DJIA at the time. Since the market events took place in electronic markets, and algorithmic trading and high-frequency trading, parts of FinTech, played significant roles, we handle the May 6 flash crash from the FinTech, SupTech, and financial supervision perspectives. With the flashback method, we analyzed the reactions of market participants, media, and two financial supervisors, the SEC, and the CFTC, to the market crash. We find that the technological imbalance between financial markets or institutions and their supervisors drove the markets in uncertainty, hence in a fear and panic environment. Since the imbalance has not diminished yet, the same risks still exist. As a remedy, we introduce a new concept and model with a well-functioning SupTech system to cope with the May 6 type FinTech crises.
Keywords: D47; D53; G18; G01; G28; H11; K22; K23; L15; O31; O32; 340; Supervisory technology; SupTech; FinTech; RegTech; Financial supervision; Financial system; Prudential supervisory disclosure; Financial authority; Digital finance; May 6 flash crash; FinTech crises; Financial crises; Financial stability; Informational efficiency; Systemically important data; Systemically important markets; Know-your-data; Know-your-technology; Know-your-markets; Inform-your-markets